The way things work. Heat [videorecording (DVD)] - Zamora, Diego; Macaulay, David (Schlessinger Media, 2003)
A visiting inventor discovers just how useful Mammoth Island's mammoth population is in keeping things warm one freezing winter day. The Islanders learn that heat can travel from one place to another in three ways: conduction, convection, or radiation.